Peer Feedback as a Future Competence: Improving Reflective Practice-based Learning - Thorup, Charlotte Brun; Nielsen, Lene Stumph; Larsen, Louise Landbo; Kristiansen, Jette; Thomassen, Tanja; Pristed, Sofie Gry; Maimburg, Rikke Damkjær; Dau, Susanne (Proceedings for the European Conference on Reflective Practice-based Learning 2025, 2025)
Background In clinical health education, limited time and resources for supervision often hinder students’ development of professional competencies and reflective practice. Reflective Practice-Based Learning (RPL) emphasises peer learning and feedback as potential strategies to enhance knowledge sharing and competence development. However, empirical evidence on the strengths and limitations of peer feedback in healthcare remains scarce. This study explores how students and clinical supervisors experience formal and informal peer activities and their influence on student learning. Method Data were collected through six semi-structured interviews involving 32 students and 13 clinical supervisors from nursing and physiotherapy programs. Thematic analysis was conducted following Braun and Clarke’s framework. Two health education students were involved throughout the research process, contributing to the development of the interview guide and the analysis. Results Four themes emerged: (1) Creating a safe learning environment, (2) Learning through peer activities, (3) Possibilities and limitations for peer feedback, and (4) Positions in clinical practice. Peer activities were perceived as informal and equal, fostering open dialogue, reflection, and critical thinking. Students reported enhanced academic and clinical learning, including leadership development. However, peer learning alone may risk exclusion from the broader clinical community. The findings underscore the importance of structured frameworks, clearly defined roles, and adequate preparation for effective peer feedback. Junior students benefit from experienced peers, while senior students gain from providing feedback. Limitations include uneven responsibility distribution, skill gaps, and organisational challenges. Conclusion Peer learning should be viewed as a complementary approach within clinical education, supported by institutional structures and supervisory engagement.